Analysis of hand-foot/leg preferences and laterality in movement difficulties of individual elite rhythmic gymnasts - Aydin, E.; Go¨nkek, P.; Kilinçkaya, E.; Akkent, C. G.; Bayer, K.; Kutlay, E. (Science of Gymnastics Journal, 2023)
The aim of this study is to determine the number and ratio of hand-foot/leg preferences in movement difficulties used by individual elite senior rhythmic gymnasts in their routines. In the World Cup Competitions and European Championships held in 2021, the final competition routines (N=75) of gymnasts (N=28) were examined, and body and apparatus difficulties, and the number and rate of use of the preferred side were determined. Since gymnasts participated in more than one competition, their most recent competition routines were included in the research. The data were obtained by analyzing the routines recorded during the competitions. Explanatory statistical analyses of the data were conducted by using the IBM SPSS 25.0 statistical program. In all routines, while higher rates of between 56.2% and 87% were found in the right hand when compared to the left hand in throwing and catching, higher rates were found in the hoop and ribbon apparatus in throwing with the left foot when compared to the right foot. In the right foot/leg catches, the highest rates were observed in the hoop apparatus (49.6%). Left foot usage preferences were observed at rates varying between 65.1% and 97.4% in jumps/leaps difficulties and between 58% and 71% in balance difficulties. In rotation difficulties, the use of the right foot had higher rates of between 72.6% and 80% when compared to the left foot. Gymnasts showed a tendency to use the right hand predominantly in throws and catches, the left foot in jumps/leaps and balances, and the right foot in rotations.